Identification of Carotenoids in Halimeda macroloba Reef Associated Bacteria - Wiwik Astuti; Ocky Karna Radjasa; Ferry Fredy Karwur; Ferdy S. Rondonuwu (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Several carotenoid pigments which are produced by sea microorganisms are shown to function as antimicrobe compounds and potential antioxidants. Coral reefs with high levels of diverse biota facilitate Halimeda as a primary component and producer to have associated bacteria that produce relatively unknown metabolic compounds. This research attempts to isolate bacteria that are associated with Halimeda macroloba, identify it, as well as analyze the pigment content produced. A yellow-orange bacteria colony is successfully isolated and given the temporary name MK_HM. This bacteria is in the shape of circular (oval) rods and are gram-variable bacteria. Based on the sequencing analytical results, Blast homology, as well as a phylogenetic analysis, it shows that the bacteria have a relationship with Exiguobacterium aestuarii TF-16 at 94%, so that it can be strongly predicted that the MK_HM strain is a new species. This pigment analysis, which is conducted on the Exiguobacterium sp. MK_HM bacteria extract, reveals that this strain produces carotenoid pigments of diadinochrome, semi-α-carotenone, dinoxanthin, and P457. Keywords: Exiguobacterium, carotenoid, diadinochrome, semi-α-carotenone, dinoxanthin, and P457.